Effect of Kinesio Taping on Muscle Spasticity in Post-Stroke Patients Receiving Infrared Therapy and Stretching Exercise : A Quasi-Experimental Study - Riswanti, Andirezeki; Kartadinata, Robby Tjandra; Julianti, Hari Peni; Zuhdiana, Hindun; Wibisono, Lilik Sigit (RSUP Dr. Kariadi, 2023)
BACKGROUND: Spasticity is one of the symptoms of a stroke. One of the muscles with increased tone is the plantar flexor (66%). Spasticity is commonly treated with infrared therapy and stretching exercises. Kinesio Taping is a skin-based therapeutic procedure that uses elastic tape and can be used with infrared therapy and stretching exercises. Kinesio Taping is predicted to reduce spasticity in the plantar flexor muscle as determined by the Tardieu scale, improving functional walking. OBJECTIVE: To demonstrate the efficacy of adding Kinesio Taping on lower extremity muscular spasticity in post-stroke patients who had previously received infrared and stretching exercises. METHOD: This study is a controlled group design with a quasi experimental pre and post test. Post-stroke patients were divided into two groups: the control group (16 patients) and the treatment group (16 patients) who received the addition of Kinesio Taping. Before and after 6 weeks of treatment, the Tardieu scale was measured. RESULT: Before and after treatment, there was a significant difference in Tardieu scale (both on quality and angle of resistance) in each group (p < 0.05), and there was a significant difference in Tardieu scale in the two groups (p < 0.05). CONCLUSION : Kinesio Taping has been demonstrated to significantly reduce plantar flexor muscle spasticity in stroke survivors.